Letters to the Editor (International Library of African Music, 1962)
From: J. V. Owen, Rev. A. M. Jones, Dr. John Carrington, Gerhard Kubik, Missao S. Jose de Mitucue, Rev. B. Kingslake, Dr. The Rev. Brother Basil, Darius L. Thieme, Fr. Ch. v. Rÿthoven, J. H. Kwabena Nketia, Andrew Tracey.
Keywords: African Music